1996
DOI: 10.3382/ps.0751109
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethoxyquin on Tissue Peroxidation and Immune Status of Single Comb White Leghorn Cockerels

Abstract: The responses to supplementing the diet of Single Comb White Leghorn (SCWL) cockerels with ethoxyquin were tested on two parameters: 1) tissue peroxidation and 2) immune response. In the first experiment, three concentrations of supplemental ethoxyquin (0, 500, and 1,000 ppm) were added to a basal diet and fed to SCWL cockerels for 6 wk. Tissue peroxidation was assessed by measuring the thiobarbituric acid reactive substances (TBARS) concentration in the liver, kidney, heart, and spleen. The TBARS concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Esses resultados corroboram os descritos por Bailey et al (1996), que não verificaram influência dos níveis de oxidação do óleo testado sobre o peso absoluto do fígado das aves.…”
Section: Resultsunclassified
“…Esses resultados corroboram os descritos por Bailey et al (1996), que não verificaram influência dos níveis de oxidação do óleo testado sobre o peso absoluto do fígado das aves.…”
Section: Resultsunclassified
“…In the absence of vitamin E and ethoxyquin fertility and sperm concentration were reduced; both dosages of ethoxyquin or vitamin E fed after 38 weeks of vitamin E depletion restored fertility and semen concentration to values comparable to males fed vitamin E or ethoxyquin continuously; the lower dosages of vitamin E (32 mg/kg feed) or ethoxyquin maintained fertility and sperm concentration over the 50-week experiment; and no statistically significant differences were observed in semen volume, hatchability of fertile eggs, feed consumption, body weights or dead sperm. Bailey et al (1996) in young chicks from day-old to 6 or 8 weeks of age used up to 1000 mg/kg ethoxyquin in nutritionally adequate diets, and found no signs of toxicity on any health or performance parameter except significantly higher relative liver weights in the groups receiving 1000 mg ethoxyquin/kg feed in the second (8-week) study. The relative liver weights were 2.8 %, 2.7 %, 2.6 % and 3.1 %, in the groups receiving 0, 125, 500 and 1 000 mg ethoxyquin/kg feed.…”
Section: Safety For Chickens For Fattening and Breedersmentioning
confidence: 94%
“…For example, Woodall et al (1996) found no significant differences in weight gain of broiler fed Vit E or several supplementary carotenoids. Jakobsen et al (1994) found no differences in weight gain of poultry supplemented with Vit E. Bailey et al (1996) found no differences in weight gain in poultry whose food had been supplemented with ethoxyquin. In addition, Biswass and Wakita (2001) found that supplementation with green tea polyphenols maintained or lowered weight gain in broilers, and Goñi et al (2007) reported that broilers supplemented with grape pomace exhibited no differences in growth performance.…”
Section: Discussionmentioning
confidence: 94%